Political Dimension of Globalization and its Effects on Nation-State - Bournane, Omar (Journal of Legal Studies and Researches, 2022)
This study tends to analyze the various aspects of globalization, in particular its effects on the political field. Globalization has positive effects as bringing peoples closer but negative ones too such as the threatening of Nation-State concept by endangering its sovereignty. Thus, developing countries have to find new efficient mechanisms to ensure their sustainability and avoiding the exploitation of their wealth by those developed ones.